Aircraft NCAR C-130 High-rate Data (netCDF) [NCAR/RAF] - NCAR/EOL Research Aviation Facility (Arctic Data Center, 2009)
High-rate data in netCDF format is available here for each flight of the NCAR C-130 that occurred during the SHEBA project (16 flights total) in the spring and summer of 1998. The following is a list of research flight numbers and corresponding dates/times: (rf01a 1846 5/4/98 - 0017 5/5) (rf01b 0036 5/5 - 0350 5/5) (rf02 1849 5/7 - 0220 5/8) (rf03 1808 5/11 - 0312 5/12) (rf04 1824 5/15 - 0256 5/16) (rf05 1652 5/18 - 0330 5/19) (rf06 1655 5/20 - 0300 5/21) (rf07 1653 5/24 - 0327 5/25) (rf08 1652 5/27 - 0312 5/28) (rf09 1630 7/8 - 0318 7/9) (rf10 1658 7/15 - 0250 7/16) (rf11 1635 7/18 - 0335 7/19) (rf12 1608 7/21 - 0254 7/22) (rf13 1627 7/23 - 0332 7/24) (rf14 1547 7/26 - 0004 7/27) (rf15 1556 7/28 - 0003 7/29) (rf16 1658 7/29 - 0004 7/30). The SHEBA C-130 dataset documentation (most of the materials made available in the previously-released data notebooks) have been put on-line via the NCAR RAF Web site. This will enable all users of the data to access the most critical documentation and data quality materials and to assemble their own copies of the documentation package. This documentation web site may be reached by selecting the data set named SHEBA: Aircraft NCAR C-130 Documentation and Data Quality Materials.